A Systematic Review of Servant Leadership Outcomes in Education Context - Kainde, Sandra J.R.; Mandagi, Deske (LP. Ma'arif Janggan Magetan, 2023)
This study presents a comprehensive systematic review aimed at investigating the role of servant leadership within the context of education. The primary objective was to identify and synthesize empirical studies exploring the outcomes and impacts of servant leadership in educational settings. Given the paucity of systematic reviews addressing servant leadership in education, this research seeks to bridge the gap in existing literature by providing an evidence-informed exploration of how servant leadership operates and can be effectively applied in educational institutions. The study employed a systematic literature review methodology, analyzing 30 scientific articles sourced from the Scopus and Web of Science (WOS) databases. The results of the data analysis highlighted the critical role played by servant leadership in the education context. At the individual level, servant leadership fosters a vibrant environment where teachers experience enhanced morale, job satisfaction, and engagement. Trust and loyalty flourish, solidifying the bonds within the educational community. On the organizational level, servant leadership empowers individuals and fosters improved communication, leading to a positive and collaborative organizational culture. The findings underscore the profound impact of servant leadership on teacher outcomes, affirming its relevance as a guiding philosophy for effective leadership within educational settings.